다양한 광원 조사에 따른 curcumin의 광안정성과 산화방지 활성의 변화 및 유화안정제에 의한 조절 - 김혜린; 홍정일 (한국식품과학회지, 57(3), 2025)
Curcumin exhibits various bioactive functions but is chemically unstable and poorly soluble in water. This study investigated the effects of different emulsion stabilizers including polyvinyl alcohol (PVA), polyethylene glycol, polysorbate 80 (PS), sucrose stearate, and lecithin on the color intensity, photostability, and antioxidant properties of curcumin. PVA and PS significantly enhanced the color intensity of curcumin. Additionally, color degradation was accelerated under light exposure in the following order: blue light emitting diode (LED), fluorescent light, white LED, green LED, and red LED irradiation. PVA significantly delayed the color degradation of curcumin under all the tested light sources. PS also improved the photostability of curcumin under green LED irradiation but not under other light sources. The antioxidant activity of curcumin, assessed through 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) and 2,2'-azobis(2-amidinopropane) dihydrochloride radical scavenging assays, was enhanced in the presence of PVA. These results indicate that different emulsion stabilizers modulate the solubility, photostability, and bioactivity of curcumin in aqueous solutions. KCI Citation Count: 0